How does a city’s digital economy development impact pollution emissions? - Lan, Tian; Ma, Jun (Frontiers in Environmental Science, 2025)
IntroductionThis study investigates the impact of urban digital economy development on pollution emissions across 285 Chinese cities from 2002-2022.MethodsUtilising threshold regression, spatial autoregressive, and mediation models, we identify a nonlinear inverted U-shaped relationship where initial digital expansion initially elevates emissions before mature digital ecosystems drive reductions.ResultsSpatial heterogeneity reveals significant emission reductions in eastern/central regions versus limited effects in western/northeastern areas, while spatial spillover effects necessitate inter-regional policy coordination. Mediation analysis highlights green technology innovation and industrial upgrading as critical mitigating mechanisms.DiscussionFindings advocate context-specific policies prioritising energy efficiency during digital emergence and advanced technology promotion in mature contexts, providing empirical groundwork for balancing digital economic benefits with environmental sustainability objectives.